AB0342 Serum Transferrin Receptor Ratio to Serum Ferritin and Hepcidin Levels in the Differential Diagnosis of Anemia in Rheumatoid Arthritis Patients. (9th June 2015) - Nita, E.; Kyratzopoulou, E.; Eliadis, P.; Makatsori, D.; Kostara, C.; Mitsioni, A.; Tsaousi, C.; Levidiotou, S.; Bairaktari, E.; Mamalaki, A.; Voulgari, P.V.
Abstract : Background: Anemia of chronic disease (ACD) is an extra-articular manifestation of rheumatoid arthritis (RA) that is due to proinflammatory stimuli by inhibition of erythropoiesis directly and indirectly by decreasing the iron available for heme synthesis. ACD and iron deficiency anemia (IDA) often occur concurrently and often leads to a diagnostic dilemma. The assessment of the anemia is based on hemoglobin content parameters, serum levels of iron, ferritin, total iron binding capacity (TIBC) and saturation of ferritin, parameters that are often directly affected by inflammation, hindering clinical interpretation. Soluble transferrin receptor (sTfR) levels indicate iron deficiency and are unaffected by inflammation while, sTfR/log ferritin index (sTfR Index) provides an estimate of body iron over a wide range of normal and depleted iron stores. Hepcidin, a liver- derived acute-phase reactant is a key mediator of ACD. Objectives: The aim of this study is to estimate the ability of hepcidin, sTfR and sTfR/log ferritin index to improve differential diagnosis of ACD and IDA in RA patients Methods: Serum samples from 38 RA patients (29 women and 9 men) with mean age ± SD 68.79±12.64 years, with anemia (Hb<12 gr/dl for women and Hb<13gr/dl for men) were collected after an overnight fast. Forty healthy individuals, age and gender matched, were used as a control group. Total blood count, conventional biochemical parameters and serum levels of ferritin (ng/ml) and sTfR (nmol/L) were measured according to standard procedures. Serum hepcidin levels were measured using a competitive in-house ELISA developed by our group. The patients with rheumatoid arthritis were divided into two groups according to the levels of sTfR Index. A cutoff value of sTfR/log fer≥14 has been used as prognostic for the presence of IDA. Results: Patients with RA presented higher levels of hepcidin (59.95±20.79 vs 22.72±10.81 μg/l) and higher levels of sTfR/logfer (23.73±41.4 vs 7.07±2.93) compared to healthy individuals. Patients with sTfR/log fer≥14 presented marginary significantly lower levels of hepcidin (55, 95±15, 66 μg/l) than patients with sTfR/log fer<14 (61, 17±23, 77 mg/L). Conclusions: These results indicate that hepcidin levels can enhance the distinctive role of StfR/logFer index leading to a better and safer distinction of RA anemic patients with IDA, IDA+ACD or ACD. Acknowledgements: This work was supported by grant from the Greek General Secretariat of Research and Technology 09SYN-12-682 Disclosure of Interest: None declared